BANK SEBAGAI KREDITUR SEPARATIS DALAM PENGAJUAN PERMOHONAN PAILIT (Studi Kasus Putusan Pailit Nomor : 16/Pailit/2011/PN.Niaga.Mdn) - Andreas Iriando Napitupulu; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2018)
ABSTRACT Settlement of accounts payable through bankruptcy institutions is intended to obtain a proportional distribution for creditors. But for separatist creditors, there is a possibility that the separatist creditor is not fully felt, namely in relation to the execution rights that take precedence. If the debtor's due date is not paid, the creditor can use the right of execution to sell the collateral that is under his control, the result of which is to pay off the debtor's debt. To exercise this right, whether a separatist creditor can execute directly or file a bankruptcy request against his debtor in court. In this regard, the problem arises is how is the position of the bank as creditor in filing a bankruptcy application and bank position in bankruptcy decision number: 16 / Bankruptcy/2011/PN.Niaga.Mdn and the legal considerations of the judges in the decision number: 16/Pailit/2011/PN.Niaga.Mdn between PT. Bank Negara Indonesia (Persero) Tbk. with PT. Serba Indah Aneka Pangan. The research method used is normative juridical research using secondary data obtained from library data collection techniques (library research) in analyzing decision No. : 16 / Pailit / 2011 / PN.Niaga.Mdn. This research is analytical descriptive, where the whole analytical is done using qualitative analysis to reveal in depth the views, concepts and will be comprehensively decomposed to answer the problems of this thesis, and conclusions are drawn using the deductive approach. Legal relationship PT. Bank Negara Indonesia (Persero), Tbk., with PT. Serba Indah Aneka Pangan is a credit agreement with material guarantees namely fiduciary guarantee and mortgage rights. PT. Bank Negara Indonesia (Persero), Tbk., As a separatist creditor has the right to submit bankruptcy applications to debtors who do not fulfill certain debts or obligations at a specified time and can be billed. The separatist creditor is the holder of the material security right that can execute the collateral object that is guaranteed to him, as if there was no bankruptcy. Basically this has given a special privilege to separatist creditors, so as not to be affected by bankruptcy in the debtor. However, with this privilege already granted, separatist creditors can apply for bankruptcy for their debtors as referred to in Article 2 Paragraph (1) UUK and Explanation of Article 2 Paragraph (1) UUK. The application of the law by the panel of judges in the application for the statement of bankruptcy in the bankruptcy decision No .: 16/Pailit/2011/PN.Niaga.Mdn is correct and has provided legal certainty and legal justice. The realization of legal certainty will prevent inconsistencies in decisions, so that decisions on the case can be predicted by justice seekers. The existence of a consistent decision, legal certainty and legal justice can be realized. Keywords : bankruptcy, separatist creditor, bank